A semi-continuum model for fluid imbibition under nanoconfinement: Assessing fluid velocity jumps and meniscus acceleration - Cencha, Luisa Guadalupe (2025)
Fluid imbibition under nanoconfinement exhibits dynamics that significantly deviate from classical continuum predictions, posing unique challenges in understanding nanoscale transport phenomena. This study presents a semi-continuum model for capillary imbibition of simple fluids in nanochannels, addressing the limitations of traditional frameworks like the Lucas–Washburn model. By incorporating sub-continuum effects—such as precursor films and fluid slippage at the walls—into continuum equations, our model captures molecular-scale phenomena that dominate in confined spaces. Key findings include the prediction of fluid velocity jumps and meniscus acceleration, driven by the interplay between confinement and the precursor film´s influence on meniscus curvature and fluid distribution. These anomalies, which contradict classical expectations, are validated against molecular dynamics simulations from the literature. The model offers a robust framework for interpreting nanoscale fluid behavior.